Pengaruh Penggunaan Ekstrak Kayu Secang (Caesalpinia sappan L.) terhadap Uji Organoleptik dan Kadar Air Albumen Telur Asin Itik Magelang - Nur Hidayah (Universitas Islam Negeri Alauddin Makassar, 2022)
Duck is one type of waterfowl that has a higher nutritional content than chicken. The high nutritional content of duck meat causes the meat to be more easily damaged because there is enough food for microbes so that duck meat cannot be stored at room temperature for too long. An alternative effort to inhibit microbial activity in duck meat is the addition of safe natural ingredients to the meat. One of the natural ingredients that can be used is bilimbi fruit because it has a high acid content. This study aims to determine the difference in the duration of soaking Magelang duck meat with belimbing wuluh juice on the pH value, water holding capacity and water content. The research method was carried out using a Completely Randomized Design (CRD) with 4 treatments and 5 replications, and using a 40% concentration of bilimbi fruit juice with a soaking time of 0, 20, 40, 60 minutes. The data obtained were analyzed by analysis of variance (ANOVA) and if different results were obtained, it was continued with the Duncan Multiple Rang Test (DMRT) further test. The results showed that the immersion time for 20-60 minutes had a very significant effect on lowering the pH value (4.30-4.67) and significantly reduced water content (63.83-64.07%) with a time 40-60 minutes, but had no significant effect on water holding capacity (54.63-48.47%). The immersion time of 40-60 minutes with bilimbi fruit juice with a concentration of 40% in Magelang duck breast meat reduced pH and water content, but had no effect on water holding capacity.